2015
DOI: 10.3390/s150305982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Detection Characteristics of Trace Species Using Laser-Induced Breakdown Spectroscopy and Laser Breakdown Time-of-Flight Mass Spectrometry

Abstract: The rapid and precise element measurement of trace species, such as mercury, iodine, strontium, cesium, etc. is imperative for various applications, especially for industrial needs. The elements mercury and iodine were measured by two detection methods for comparison of the corresponding detection features. A laser beam was focused to induce plasma. Emission and ion signals were detected using laser-induced breakdown spectroscopy (LIBS) and laser breakdown time-of-flight mass spectrometry (LB-TOFMS). Multi-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This result indicates that with the increase of Hg concentration in the mixed gas, the change of noise was relatively small, and the interference of noise on Hg signal intensity measured by different Hg concentrations was relatively stable. The Hg detection limit was estimated by evaluating the ratio of standard deviation of noise to the slope of the Hg calibration curve [24,25]. The detection limit of the Hg signal was around 0.06 ppm (0.32 mg•m -3 ) at a gas pressure of 10 kPa in this study.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This result indicates that with the increase of Hg concentration in the mixed gas, the change of noise was relatively small, and the interference of noise on Hg signal intensity measured by different Hg concentrations was relatively stable. The Hg detection limit was estimated by evaluating the ratio of standard deviation of noise to the slope of the Hg calibration curve [24,25]. The detection limit of the Hg signal was around 0.06 ppm (0.32 mg•m -3 ) at a gas pressure of 10 kPa in this study.…”
Section: Resultsmentioning
confidence: 69%
“…Gleason et al [22] found that the 253.7 nm mercury emission intensity had a significant reduction with the introduction of an oxygen-containing species in long decay times, and the 253.7 nm mercury emission line was selectively quenched by oxygen species, primarily O 2 and NO. Wang et al analyzed the detection characteristics of LIBS for trace heavy metal mercury under low pressure and short pulse conditions [23][24][25]. The results showed that NO formed by O 2 and N 2 in the plasma cooling process produced the electron transition of an NO emission band centered at 258 nm, which seriously interfered with the Hg signal.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these techniques are more expensive, time consuming and not suitable for in-situ and point to point detection analysis Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Laser Induced Breakdown Spectroscopy (LIBS) has been introduced as a valuable tool for in-situ and in-vivo analysis of any type of materials including plants (Chauhan et al, 2011a(Chauhan et al, , 2011bTripathi et al, 2011Tripathi et al, , 2012Kumar et al, 2013;Maurya et al, 2014;Wang et al, 2015). LIBS is based on collection of the emission from ionic, atomic and molecular species in the plasma formed due to high power laser and material interaction ( Rai et al, 2009;Tripathi et al, 2012;Devey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Various papers reported the signal enhancement by optimizing the experimental conditions to improve LIBS detection ability, such as pulse width, laser wavelength, laser power, gate delay time, lens-to-sample distances, atmospheric condition, etc. [7][8][9][10][11] Some improvement approaches of the LIBS technique have also been developed, such as dual-pulse LIBS (DP-LIBS), [12][13][14][15] resonanceenhanced LIBS (RE-LIBS), 16,17 laser ablation fast pulse discharge plasma spectroscopy (LA-FPDPS), 18,19 microwave-assisted LIBS (MA-LIBS), 20 LIBS laser-induced fluorescence (LIBS-LIF), 21 and other combination methods. Dual-pulse LIBS is an important way to enhance the emission intensities to improve LIBS analytical capability.…”
Section: Introductionmentioning
confidence: 99%